Challenging paradigms: integrating Critical Feminist Service-Learning into Higher Education Physical Activity and Sport programs - Nuria Cuenca Soto; María Luisa Santos-Pastor; Oscar Chiva-Bartoll; Luis Fernando Martínez-Muñoz (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Over the past decades, public policies have aimed to promote gender equality and a gender perspective in educational and research settings. However, Higher Education shows significant deficiencies in gender-related training in its curricula. This article aims to define the pedagogical model called Critical Feminist Service-Learning, presenting a series of keys that allow feminist theories to be applied in real-life contexts within the framework of Physical Activity and Sports. This model facilitates educational advancements through transformative approaches that prioritize gender equity and social justice. Focused on the teaching of Physical Activity and Sports, it explores the confluence of various feminist philosophies and theories in Service-Learning, aligning with the principles of feminist pedagogies. While recognizing the successes of this Service-Learning approach, a call is made for a text that consolidates and synthesizes this perspective, proposing a clear general model as described here. In contrast to the prevailing model, the traditional charity-oriented Service-Learning that predominates in educational institutions, Critical Feminist Service-Learning includes all participants as beneficiaries. It critiques hierarchical society, recognizes underrepresented groups and voices, moving away from structures that reinforce social orders and structural oppression. The advocated pedagogical model here offers a practical solution to promote gender equality and social justice in educational and research environments, specifically in the context of Physical Activity and Sports, promoting the use of transformative pedagogies in Higher Education.